Molecular Diagnosis of Vaginal Microbiota Associated with Spontaneous Abortion in Women - Al-Hajjar, Enas Lateef Noor; Al-Bermani, Oruba K.; Witwit, Suha J (Iraqi Journal of Science, 2024)
Spontaneous abortion (SA) is a sever disease in which a women losses her foetus usually before 24 weeks of the pregnancy. About 10% -50% of pregnancy cases are run out with SA for reasons related with women's age and health. This condition occurrence may increases if the patient has a history of bacterial vaginosis. This study aimed at the characterization and isolation of vaginal microbiota generally and highlight on commensal bacteria becoming opportunistic when circumstances are favourable. From October to December 2022, about 100 samples were collected, 50 specimens from women with SA and 50 specimens from healthy pregnant outcomes (control). The high vaginal swabs samples were collected from Babylon Teaching Hospital for Maternity and Children and Imam Sadiq Teaching Hospital in Babylon, Iraq. To culture the samples, they were transported by media swab to laboratory. The culture of bacteria was done on 4 types of agar media: UTI chromogenic agar, MRS agar, MacConkey agar and blood agar. The first identification of bacteria was based on phenotypic traits of colonies, using manual biochemical tests and gram stain. Finally, the diagnosis was confirmed genetically by extracting bacterial genomic DNA for 20 of bacterial isolates under study and using PCR technique for 16S rRNA Loci gene and sequencing. The current study results showed difference in bacterial genera in women with SA compared with healthy women. It was also noted that embroilment of Enterococcus faecalis occurred in most cases of SA with an estimated percentage of 56% (28/50), thus defeating Escherichia coli by 32% (16/50) and 4% (2/50) for Klebsiella pneumonia and 4% (2/50) for Enterococcus gallinarum. In this study, some very rare bacteria species were identified including Acinetobacter junii at 2% (1/50) and Corynebacterium coyleae at 2% (1/50). While the percentage of bacteria associated with healthy women was: 30% (15/50) for E. faecalis, 26% (13/50) for E. coli, 18% (9/50) for K. pneumonia, 24% (12/50) for Staphylococcus epidermidis, and 2% (1/50) for Metabacillus niabensis (which was diagnosed for the first time in Iraq as well as the rest of the world in a clinical sample).